Hemianopic colour blindness. Issue 6 (June 1975) - Albert, M L; Reches, A; Silverberg, R
Abstract : A man developed cortical blindness after cerebral infarction in the distribution of both posterior cerebral arteries. When he recovered from this condition, he was found to be colour blind in the left visual field, but not in the right. This unusual situation resulted in apparently contradictory performances on hemifield and free-field tasks of colour discrimination, naming, and recognition. The contradictions may be explained by interhemispheric competition between a hemisphere which could discriminate colours and a hemisphere which was colour blind.